Understated gender disparities due to outcome-dependent selection: Commentary on Mackelprang et al. (2023) - Loh, Wen Wei; Ren, Dongning (The American psychologist, 2023)
What is the gender gap in invited publications in high-impact psychology journals? To answer this critical question, Mackelprang et al. (2023) examined invited publications in five high-impact psychology journals. They first calculated the share of women among authors of the invited publications (35.6%), then compared it with a "base rate" (42.3%; the share of women among associate and full psychology professors at R1 institutions). This comparison was presented as empirical evidence of women being underrepresented in the authorship of publications in these high-impact journals. In this commentary, we show that comparing these two descriptives-either using a difference or a ratio-provides little insight into the actual gender disparity of interest. A fundamental shortcoming of such a comparison is due to outcome-dependent selection. We explain what outcome-dependent selection is and why it is inappropriate. Crucially, we explain why, following such outcome-dependent selection, comparing the share of women in the selected sample with a "base rate" rules out drawing valid inferences about the actual gender gap. We urge researchers to recognize the perils of, and thus avoid, outcome-dependent selection. Finally, we suggest an alternative approach that permits a more accurate understanding of gender disparities in academia. (PsycInfo Database Record (c) 2023 APA, all rights reserved).